If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 3w = 4 + 9w Solving 7 + 3w = 4 + 9w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-9w' to each side of the equation. 7 + 3w + -9w = 4 + 9w + -9w Combine like terms: 3w + -9w = -6w 7 + -6w = 4 + 9w + -9w Combine like terms: 9w + -9w = 0 7 + -6w = 4 + 0 7 + -6w = 4 Add '-7' to each side of the equation. 7 + -7 + -6w = 4 + -7 Combine like terms: 7 + -7 = 0 0 + -6w = 4 + -7 -6w = 4 + -7 Combine like terms: 4 + -7 = -3 -6w = -3 Divide each side by '-6'. w = 0.5 Simplifying w = 0.5
| 2x+4=2x | | 6x-7=3(x+4)+3x | | 2s+10s=96 | | 15x-3-x=2x+21 | | w-10w= | | x^4+2x^3-32x-256=0 | | x-3=2+x | | X+4y=6 | | 8p=7(9p+2) | | 2-(3x-5)=4-2x+3-x | | 5X^2-4X=2 | | x+y+578=78(7)-x | | (3x-6)-(5x+8)=4x-20 | | 5-3k=8-4k | | 25=13-4x | | 8(3x-9)=4(6x+7) | | 0.375r-0.1875+0.75r=0.75+r | | x+8y=3 | | x+y+z=33.33 | | 15-6(2x-4)=8+2(5x-1) | | x+x=x | | 2z=-12 | | 5(6x-9)=-5 | | -9(3b+4)+(28b-3)=0 | | 4+4n-4= | | x+5=x+56x | | 15x+24=24x-2 | | -1.25+0.25x=0 | | 8.33b+7.44=25.55 | | -2x+3=13 | | 5x^2-33x-56=0 | | 4.4q-5.8-5.5q=-2.1q-5.2 |